2020
DOI: 10.3390/ijerph17134838
|View full text |Cite
|
Sign up to set email alerts
|

Involving Parents to Help Improve Children’s Energy Balance-Related Behaviours Through a School-Based Intervention

Abstract: The Challenge Me intervention aimed to indirectly involve parents in a school-based intervention, by challenging primary school children to perform physical activity (PA) and nutrition-related activities with their parents. The aim of this study is to gain insight in whether this was a feasible strategy to engage children and parents, especially those of vulnerable populations. An exploratory cross-sectional study design was applied. Four primary schools implemented the intervention. Data consisted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 47 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…Figure 2 and Table 3 summarize the results obtained. In general, direct parental involvement through modeling ( Alia et al, 2013 ; Sterret et al, 2013 ), the participation of parents and children together in sports ( Lev et al, 2020 ; Yazeedi et al, 2021 ), and the indirect participation in PA (advice sheets making or newsletters) ( Verhees et al, 2020 ) may promote active lifestyles. It is usual that when PS raises children with parental support ( Yaffe, 2018 ) and affection ( Huffman et al, 2018 ), adequate levels of PA practice are registered.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Figure 2 and Table 3 summarize the results obtained. In general, direct parental involvement through modeling ( Alia et al, 2013 ; Sterret et al, 2013 ), the participation of parents and children together in sports ( Lev et al, 2020 ; Yazeedi et al, 2021 ), and the indirect participation in PA (advice sheets making or newsletters) ( Verhees et al, 2020 ) may promote active lifestyles. It is usual that when PS raises children with parental support ( Yaffe, 2018 ) and affection ( Huffman et al, 2018 ), adequate levels of PA practice are registered.…”
Section: Resultsmentioning
confidence: 99%
“… Lev et al (2020) found that parents who exercised with their children helped perceive greater enjoyment during PA and, consequently, the children’s participation in it increased. Verhees et al (2020) found another way of involving parents in their children’s active lifestyles: indirect involvement. The indirect parental involvement in the PA of their children is carried out through the preparation of tip sheets or support bulletins and causes an increase in participation in it Verhees et al (2020) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations